Evolutionary Stability in Asymmetric Oligopoly. A Non-Walrasian Result - Wolfgang Leininger; Hamed M. Moghadam (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
It is a very well-known result that in terms of evolutionary stability the long-run outcome of a Cournot oligopoly market with finitely many firms approaches the perfectly competitive Walrasian market outcome (Vega-Redondo, 1997). However, in this paper we show that an asymmetric structure in the cost functions of firms may change the long-run outcome. Contrary to Tanaka (1999) we show that the evolutionarily stable price in an asymmetric Cournot oligopoly needs not equal the marginal cost, it may rather equal a weighted average of (different) marginal cost. We apply a symmetrization technique in order to transform the game with asymmetric firms into a symmetric oligopoly game and then extend Schaffer's definition (1988) of a finite population ESS (FPESS) to this setup. Moreover, we show that the FPESS in this game represents a stochastically stable state of an evolutionary process of imitation with experimentation. – – Einem bekannten und überraschenden Result zufolge ist das langfristige evolutionäre Gleichgewicht in einem endlichen Cournot-Opligopol durch die Allokation des vollkommenen Wettbewerbsgleichgewichts nach Walras (und nicht die des klassischen Cournot-Gleichgewichts) gekennzeichnet (Vega-Redondo, 1997). Diese Arbeit zeigt, dass dies nicht mehr zutrifft, wenn sich die Firmen asymmetrisch durch unterschiedliche Kostenfunktionen unterscheiden. Das Ergebnis wird durch die Analyse einer symmetrisierten Version des ursprünglich asymmetrischen Spiels erzeugt, in der das Lösungskonzept einer evolutionär stabilen Strategie für endliche Populationen (Schaffer, 1988) für diesen Modellrahmen adaptiert wird. Das Ergebnis widerspricht insbesondere einem Resultat von Tanaka (1999), der das "marginal cost pricing"-Resultat von Vega-Redondo für symmetrische Firmen auch auf einen asymmetrischen Fall übertragen hatte. Die vorliegende Arbeit kritisiert dessen Modell und sein Ergebnis und weist ein "average cost pricing"-Resultat als evolutionär stabile Oligopollösung nach.
Keywords: C72; C73; D43; L13; 330; Cournot oligopoly; asymmetry; finite population evolutionary stable strategy; stochastic stability